Student Timetable Mobile Application - Rizwadi Irwan, Batrisyia (IRC, 2020)
Mobile application nowadays is the most convenient way that helps the user in performing something such as tracking your health, reading books, ordering food, etc. Student Timetable mobile application is an application that focuses on UTP students as a user where they can create their own timetable for the semester that they are currently taking. The Student Timetable application is created as a mobile application to make it convenient for the students to view or make a change in their schedule anytime and anywhere. The reason behind creating this mobile application is to ease the students in creating their own class timetable for the current semester as it is hard for them to view the timetable for each course in UTPTT. Through the mobile application, the students can view the timetable easily in order to know their classes for the week. Moreover, they can also make changes through the application if there are any clashes occur. Students should find it easier to stay alert with their timetable as they can always review their timetable through the Student Timetable mobile application offline.